Recovery of oxidative stress-induced damage in Cisd2-deficient cardiomyocytes by sustained release of ferulic acid from injectable hydrogel. (October 2016) - Cheng, Yung-Hsin; Lin, Feng-Huei; Wang, Chien-Ying; Hsiao, Chen-Yuan; Chen, Hung-Ching; Kuo, Hsin-Yu; Tsai, Ting-Fen; Chiou, Shih-Hwa
Abstract: Aging-related oxidative stress is considered a major risk factor of cardiovascular diseases (CVD) and could be associated with mitochondrial dysfunction and reactive oxygen species (ROS) overproduction. Cisd2 is an outer mitochondrial membrane protein and plays an important role in controlling the lifespan of mammals. Ferulic acid (FA), a natural antioxidant, is able to improve cardiovascular functions and inhibit the pathogenetic CVD process. However, directly administering therapeutics with antioxidant molecules is challenging because of stability and bioavailability issues. In the present study, thermosensitive chitosan-gelatin-based hydrogel containing FA was used to treat Cisd2-deficient (Cisd2 −/− ) cardiomyocytes (CM) derived from induced pluripotent stem cells of Cisd2 −/− murine under oxidative stress. The results revealed that the developed hydrogel could provide a sustained release of FA and increase the cell viability. Post-treatment of FA-loaded hydrogel effectively decreased the oxidative stress-induced damage in Cisd2 −/− CM via increasing catalase activity and decreasing endogenous reactive oxygen species (ROS) production. The in vivo biocompatibility of FA-loaded hydrogel was confirmed in subcutaneously injected rabbits and intramyocardially injected Cisd2 −/− mice. These results suggest that the thermosensitive FA-loaded hydrogel could rescue Cisd2 −/− CM from oxidative stress-induced damage and may have potential applications in the future treatment of CVD.